Large wood supports Elwha revegetation by reducing ungulate browsing - Johnson, Caelan; Douglas, Chelsea; Mansmith, Trevor; McLaughlin, John (Frontiers in Ecology and Evolution, 2023)
The increasing number of dams approaching obsolescence drives a need for knowledge about riparian restoration associated with dam removal. Restoring woody vegetation on exposed reservoir beds following dam removal is essential to stabilizing sediment, reconnecting riverine and terrestrial systems, and providing future sources of shade, nutrients, and wood. Revegetation after dam removal on many rivers can be challenging due to rapidly drying sediment, low sediment nutrient content, and heavy ungulate browse pressure. Revegetation in Elwha River restoration, the largest dam removal to date, used large woody debris (LWD) to mitigate moisture and nutrient limitation but ungulate browsing has constrained woody plant growth in many coarse sediment deposits. We evaluated potential for LWD to reduce ungulate browsing following Elwha dam removal. We studied LWD mitigation of browsing in the largest former reservoir and a comparable valley upriver with a natural floodplain. We measured browse intensity in randomly located plots stratified by four levels of LWD extent, from no LWD to complete LWD enclosure. LWD reduced browse intensity four-fold in the former reservoir, but only in plots fully surrounded by LWD. Partial LWD enclosure provided little browse reduction. We obtained similar results in the upriver valley, where browse intensity was somewhat lower except within wood clusters. Wood-mediated browse reduction was slightly greater in the former reservoir than in the upriver valley. Protection from browse was greatest for plant species preferred by ungulates. These results suggest forest restoration after dam removal can be expedited by surrounding young trees with large logs. Planting within LWD clusters or placing LWD clusters in restoration sites can facilitate establishment of forest islands in strategic locations. These forest islands can support dispersal of seeds and marine derived nutrients, reconnect established forest to the river, and potentially advance restoration by decades.